Risk Factors for Recovery of Ampicillin-Sulbactam-Resistant Escherichia coli in Hospitalized Patients - Kaye, Keith S. (American Society for Microbiology, 2000)
Ampicillin-sulbactam resistance in Escherichia coli is an emerging problem. This study determined risk factors for the recovery of ampicillin-sulbactam-resistant E. coli in hospitalized patients. A case-control design was used to compare two groups of case patients with control patients. The first group of case patients consisted of patients from whom nosocomially acquired ampicillin-sulbactam-resistant E. coli strains were isolated, and the second group of case patients consisted of patients from whom ampicillin-sulbactam-susceptible E. coli strains were isolated. Control patients were a random selection among 5% of all patients admitted during the same time period. Risk factors analyzed included antimicrobial drug exposure, comorbid conditions, and demographics. Univariate and multivariate analyses were performed. Ampicillin-sulbactam-resistant E. coli strains were isolated from 175 patients, and ampicillin-sulbactam-susceptible E. coli strains were isolated from 577 patients. Nine hundred thirty-four control patients were selected. Exposure to penicillin antibiotics as a class and to ampicillin and ampicillin-sulbactam individually were the only significant, independent risk factors associated with the isolation of ampicillin-sulbactam-resistant E. coli (odds ratio [OR] = 2.32 [P < 0.001], OR = 3.04 [P = 0.02], and OR = 1.72 [P = 0.04], respectively), but they were not associated with the isolation of ampicillin-sulbactam-susceptible E. coli. Interestingly, exposure to piperacillin-tazobactam tended to protect against the isolation of E. coli strains resistant to ampicillin-sulbactam, but this did not reach statistical significance (OR = 0.13; P = 0.11).